Bone mineral density changes in NCAA Division I female acrobatics & tumbling athletes across collegiate career - Pickler, M. C.; Gallucci, A. R.; Lee, K. M.; Bolden, L. K.; Tinsley, G. M. (International Journal of Exercise Science Conference Proceedings, 2026)
Acrobatics and tumbling (A&T) has gained significant attention since becoming an official National Collegiate Athletic Association (NCAA) sport about a decade ago. The sport requires elite-level athletic abilities to perform tosses, lifts, and tumbling, making maintaining optimal body composition a key priority. However, little is known about the longitudinal impacts of the sport`s elite training and competition on specific aspects of body composition of its athletes.